67.1k views
5 votes
The measures of the angles of a triangle are shown in the figure below solve for x(6x-3)90(9x-12)

1 Answer

6 votes

x=13

1) Considering that (6x -3), 90 and (9x -12) we can write since the sum of the interior angles of any triangle is equal to 180º

6x -3 +90 +9x -12= 180 Combine Like terms

15x -15 = 180 Add 15 to both sides

15x = 180 +15

15x = 195 Divide both sides by 15

x=13

2) So x = 13 to satisfy the triangle anglular condition, i.e. the sum of their angles is 180º

User Kian
by
5.2k points